Graphene and silicene quantum dots for nanomedical diagnostics. Issue 2 (3rd January 2020) - Drissi, L. B.; Ouarrad, H.; Ramadan, F. Z.; Fritzsche, W.
Abstract : In the present work, the prominent effects of edge functionalization, size variation and base material on the structural, electronic and optical properties of diamond shaped graphene and silicene quantum dots are investigated. Abstract : In the present work, the prominent effects of edge functionalization, size variation and base material on the structural, electronic and optical properties of diamond shaped graphene and silicene quantum dots are investigated. Three functional groups, namely (–CH3, –OH and –COOH) are investigated using the first principles calculations based on the density functional, time-dependent density functional and many-body perturbation theories. Both the HOMO–LUMO energy gap, the optical absorption and the photoluminescence are clearly modulated upon functionalization compared to the H-passivated counterparts. Besides the functional group, the geometric distortion induced in some QDs also influences their optical features ranging from near ultra-violet to near infra-red. All these results indicate that edge-functionalizations provide a favorable key factor for adjusting the optoelectronic properties of quantum dots for a wide variety of nanomedical applications, including in vitro and in vivo bioimaging in medical diagnostics and therapy.